A new species of Alpheus Fabricius, 1798 (Decapoda: Caridea: Alpheidae) from the Caribbean coast of Panama - Anker, Arthur; Leray, Matthieu; Pachelle, Paulo P.g. (Zootaxa, 2021)
Alpheus viserion sp. n. is described based on the material from Bocas del Toro archipelago on the Caribbean coast of Panama. The new species is morphologically closest to three members of the speciose A. armillatus H. Milne-Edwards, 1837 species complex, viz. A. carlae Anker, 2012, A. angulosus McClure, 2002, and A. tenuis Kim & Abele, 1988, differing from them, as well as from all the other species currently included in this complex, by a suite of morphological characters and a diagnostic colour pattern. With the description of yet another new shrimp species from Bocas del Toro, the authors hope to contribute to the awareness that this archipelago represents one of the most biologically diverse places in the Caribbean Sea and to encourage the preservation of the remaining natural habitats of this unique area.